2022
DOI: 10.3390/antiox11010137
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Hydrogen Peroxide and Downstream Protein Kinase D1 Signaling Is a Common Feature of Inducers of Pancreatic Acinar-to-Ductal Metaplasia

Abstract: Pancreatic acinar-to-ductal metaplasia (ADM) is a reversible process that occurs after pancreatic injury, but becomes permanent and leads to pancreatic lesions in the presence of an oncogenic mutation in KRAS. While inflammatory macrophage-secreted chemokines, growth factors that activate epidermal growth factor receptor (EGFR) and oncogenic KRAS have been implicated in the induction of ADM, it is currently unclear whether a common underlying signaling mechanism exists that drives this process. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Pro-inflammatory macrophages are the major immune cell population driving the formation of ADM lesions ( 10 , 16 , 17 ), and their crucial role in this process was demonstrated in vivo (in mice) by genetic ablation and by chemical depletion ( 10 , 20 ). Using the KC (p48 Cre ;LSL- Kras G12D ) mouse model it was shown that during the development of pancreatic cancer these macrophages accumulate rapidly in ADM regions ( 21 ).…”
Section: Mutant Kras As An Inducer Of Macrophage Attractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pro-inflammatory macrophages are the major immune cell population driving the formation of ADM lesions ( 10 , 16 , 17 ), and their crucial role in this process was demonstrated in vivo (in mice) by genetic ablation and by chemical depletion ( 10 , 20 ). Using the KC (p48 Cre ;LSL- Kras G12D ) mouse model it was shown that during the development of pancreatic cancer these macrophages accumulate rapidly in ADM regions ( 21 ).…”
Section: Mutant Kras As An Inducer Of Macrophage Attractionmentioning
confidence: 99%
“…Moreover, M2 macrophages can drive ADM through CCL2 ( 17 ). All these factors have in common that they induce hydrogen peroxide in acinar cells, which was shown to be the major driver of ADM ( 16 , 17 ). Hydrogen peroxide most likely originates at the mitochondria, since mitochondrially-targeted catalase or the antioxidant MitoQ can block the initiation of ADM ( 16 ).…”
Section: Macrophage Secreted Factors and Oxidative Stress As Drivers ...mentioning
confidence: 99%
See 1 more Smart Citation
“…ADM can be initiated by the M1-secreted factors TNFα, CCL5/RANTES, IL-1α and IL-6 ( 12 , 34 ). A common underlying signaling event that these factors are activating in acinar cells is the increase in mitochondrially-generated reactive oxygen species (mROS) ( 35 ), which then drive ADM through transcriptional upregulation of EGFR and its ligands ( 36 ). It should be noted that oncogenic KRAS by itself is a weak inducer of ADM in ex vivo (explant) studies, also by increasing intracellular levels of mitochondrial oxidative stress and expression of EGFR ( 36 ).…”
Section: Classically Activated Inflammatory Macrophages and Their Rol...mentioning
confidence: 99%
“…The study by Döppler and colleagues [4] concerned oxidative stress and inflammation in pancreatic acinar-to-ductal metaplasia (ADM), a reversible process that occurs after pancreatic injury but becomes permanent and leads to pancreatic lesions in the presence of oncogenic mutations. In this study, the authors identified the generation of mitochondrial ROS as a common signaling pathway for the inducers of ADM.…”
mentioning
confidence: 99%